2019
DOI: 10.1038/s41419-019-2148-2
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA ODIR1 inhibits osteogenic differentiation of hUC-MSCs through the FBXO25/H2BK120ub/H3K4me3/OSX axis

Abstract: Long noncoding RNAs (lncRNAs) have been demonstrated to be important regulators during the osteogenic differentiation of mesenchymal stem cells (MSCs). We analyzed the lncRNA expression profile during osteogenic differentiation of human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) and identified a significantly downregulated lncRNA RP11-527N22.2, named osteogenic differentiation inhibitory lncRNA 1, ODIR1. In hUC-MSCs, ODIR1 knockdown significantly promoted osteogenic differentiation, whereas overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 55 publications
0
56
0
Order By: Relevance
“…In our previous study, to identify functional lncRNAs correlating with osteogenesis, lncRNA microarrays were applied to analyse lncRNA expression profiles 22 . We revealed that 20 lncRNAs were upregulated and 9 were downregulated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, to identify functional lncRNAs correlating with osteogenesis, lncRNA microarrays were applied to analyse lncRNA expression profiles 22 . We revealed that 20 lncRNAs were upregulated and 9 were downregulated.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we identified lncRNA profile during the osteogenic differentiation induction of hUC‐MSCs using Agilent Human lncRNA Microarray. A total of 23 lncRNA were significantly differentially expressed upon osteogenic differentiation 22 . Among those, LOC100506530 (the alternative name of linc02349) was significantly increased.…”
Section: Introductionmentioning
confidence: 99%
“…In present study, micro scale pores and ravines was built on the strut connection sites, which provided superior appearance environment for cells proliferation and adhesion on the scaffolds. Besides, the porous structure also provided diversified mechanical stimuli for adhered cells, thus might enhance the osteoblast differentiation [54,55]. In short, in vitro assays revealed the good cytocompatibility of SLM derived Fe-25Mn scaffold.…”
Section: The Biocompatibility Of Fe-mn Scaffoldmentioning
confidence: 99%
“…In terms of biocompatibility, as an abundant element in the human body, Zn plays a vital role in cell proliferation and the metabolism of human body [6][7][8][9]. As for biodegradability, it was reported that Zn alloys exhibited moderate degradation rate that could meet the requirements for bone repair [10][11][12][13][14]. What's more, the degradation products show good biocompatibility [15].…”
Section: Introductionmentioning
confidence: 99%